Effectiveness of treatment with surfactant in premature infants with respiratory failure and pulmonary infection - Vento, G.; Tana, M.; Tirone, et al., C. (Acta Biomedica Atenei Parmensis, 2012)
Introduction: Surfactant inactivation is present in neonatal pneumonia. Materials and Methods: One hundred thirty-nine preterm babies with BirthWeight (BW) ≤ 1250 grams were studied and subdivided in two groups: RDS Group, with a diagnosis of “simple” RDS (N 80) and RDS with Pneumonia Group, consisting of babies with a diagnosis of RDS and a positive BALF culture in the first 24-48 h of life (N 59). Outcomes: Surfactant administration seems less effective in the latter group, because a significantly higher number of infants needed a second dose of surfactant, compared to the patients suffering from RDS alone.